PENGEMBANGAN SOAL HIGHER ORDER THINKING SKILLS MATEMATIKA LINGKUP MATERI UJIAN NASIONAL SMP/MTS DI SMPN 1 MATARAM TAHUN AJARAN 2019/2020 - Qirom, Muhamad Syahidul; Sridana, Nyoman; Prayitno, Sudi (Jurnal Ilmiah Pendidikan Indonesia, 2021)
Mathematics HOTS Question has trusted can improve student’s skills in 21st century so Ministry of Education and Culture launched assessment program based on HOTS in every grade of school. The fact is at SMPN 1 Mataram the program does not run properly. There are two problems caused it happens, first the lack of teacher’s ability to build math HOTS question and the availability of HOTS question in math textbooks that used at school are not enough. This study aims to produce math HOTS question to help providing more references about math HOTS question for teacher and student at SMPN 1 Mataram. The method in this study adapt development model by Tessmer which consists two main phases, namely preliminary and formative evaluation. The result of this study has obtained 20 math HOTS question with score of validity 75.9375%, practicality 80.41%, effectiveness 79%, the diffulty index of questions in moderate category with enough discrimination power, questions also are reliable and shows the result as expected which student’s HOTS in enough category. In conclusion the study 1) has produced math HOTS questions with valid, practical, and effective category and 2) in order to develop HOTS questions, we need to consider about stimulus that are attractive, new, contextual, and it encourage student’s reasoning, in addition the questions should be connect one concept with others.